Lymphedema-associated fibroblasts are related to fibrosis and stage progression in patients and a murine microsurgical model - Will-Marks, Patrick; Kilian, Katja; Bieback, Karen; Fricke, Fabia; Berner, Juan Enrique; Kneser, Ulrich; Hirche, Christoph (Plastic and reconstructive surgery, 2024)
Background: - The driver of secondary lymphedema (SL) progression is chronic inflammation, which promotes fibrosis. Despite advances in preclinical research, a specific effector cell subpopulation as a biomarker for therapy response or stage progression is still missing for SL. - Methods: - Whole skin samples of 35 murine subjects of a microsurgically induced SL model and 12 patients with SL were collected and their fibroblasts were isolated. These lymphedema-associated fibroblasts (LAFs) were cultured in a collagen I-poly-D-lysine 3-dimensional hydrogel to mimic skin conditions. Fibroblasts from nonlymphedema skin were used as negative control and transforming growth factor β (TGF-β)-stimulated fibroblasts were used to recreate profibrotic myofibroblasts. Quantitative immunocytofluorescence confocal microscopy analysis and invasion functional assays were performed in all subpopulations and statistically compared. - Results: - In contrast to normal skin fibroblasts, LAFs exhibit α-smooth muscle actin-positive stress fibers and a reduced number of tight junctions in 3-dimensional hydrogel conditions. The switch from normal E-cadherinhigh phenotype to an N-cadherinhigh-E-cadherinlow morphology suggests epithelial-to-mesenchymal transition for expansion and proliferation. This pathologic behavior of LAF was confirmed by live cell imaging analysis of invasion assays. The significant activation of markers of the TGF-β receptor 2-Smad pathway and collagen synthesis (HSP-47 [heat shock protein 47]) in LAFs supports epithelial-to-mesenchymal transition phenotypic changes and previous findings relating to TGF-β1 and fibrosis with lymphedema. - Conclusions: - A characteristic SL myofibroblast subpopulation was identified and translationally related to fibrosis and TGF-β1-associated stage progression. This SL-related subpopulation was termed LAFs. A comprehensive stage-related characterization is required to validate LAFs as a reliable biomarker for SL disease progression. - Clinical Relevance Statement: - The authors identify a cellular effector for fibrosis and stage progression of secondary lymphedema as a possible biomarker for surgical indication and therapy response.